2013 8th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2013
DOI: 10.1109/hri.2013.6483596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of robot failures and feedback on real-time trust

Abstract: Abstract-Prior work in human trust of autonomous robots suggests the timing of reliability drops impact trust and control allocation strategies. However, trust is traditionally measured post-run, thereby masking the real-time changes in trust, reducing sensitivity to factors like inertia, and subjecting the measure to biases like the primacy-recency effect. Likewise, little is known on how feedback of robot confidence interacts in real-time with trust and control allocation strategies. An experiment to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
141
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(151 citation statements)
references
References 18 publications
8
141
2
Order By: Relevance
“…Interestingly enough, participants in a previous study with similar scenarios of emergency evacuation in simulation by the same researchers [103] behaved differently, namely participants rated less reliant simulated robots as less trustworthy and were less prone to follow them in the evacuation. The results from the simulation studies of emergency evacuation, namely positive correlation between participants' trust assessment and behavior, are similar to results in low risk studies [30]. These contradictory results point strongly that more research needs to be done to refine robot, operator and task-context variables and relations that would lead to correct trust calibration, and better understanding of the relationship between trust and performance in human robot interaction.…”
Section: Performance-based Interaction: Humans Influencing Robotssupporting
confidence: 62%
See 3 more Smart Citations
“…Interestingly enough, participants in a previous study with similar scenarios of emergency evacuation in simulation by the same researchers [103] behaved differently, namely participants rated less reliant simulated robots as less trustworthy and were less prone to follow them in the evacuation. The results from the simulation studies of emergency evacuation, namely positive correlation between participants' trust assessment and behavior, are similar to results in low risk studies [30]. These contradictory results point strongly that more research needs to be done to refine robot, operator and task-context variables and relations that would lead to correct trust calibration, and better understanding of the relationship between trust and performance in human robot interaction.…”
Section: Performance-based Interaction: Humans Influencing Robotssupporting
confidence: 62%
“…In subsequent experiments, trust ratings were collected continuously by periodic button presses indicating increase or decrease in trust. These studies [30,49] confirmed the primacy-recency bias in episodes of unreliability and the contribution of transparency in the form of confidence feedback from the robot.…”
Section: Performance-based Interaction: Humans Influencing Robotssupporting
confidence: 54%
See 2 more Smart Citations
“…This can be dangerous, because it can set unrealistic expectations: when expectations are not met, trust in the robot drops, which also impacts acceptance [22], [39], [40].…”
Section: Discussionmentioning
confidence: 99%